Perlindungan Hukum terhadap Keberadaan Guru Honorer pada Sekolah Negeri di Kota Semarang - Rahmania Siwi Perwitasari; Henny Juliani; Sri Nur Hari Susanto (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2026)
Teachers are professional personnel who play an important role in determining the quality of education; however, they still face various issues such as low wages, a shortage of teaching staff, and an increasing number of cases in which teachers encounter legal problems while performing their duties. This condition indicates the importance of regulation and legal protection, particularly for honorary teachers who, to date, still lack clarity regarding their employment status. This study aims to identify the forms of legal protection guarantees as well as the regulatory framework concerning legal protection for honorary teachers in public schools in Semarang City. The method used is empirical juridical research to identify the gap between normative provisions and their implementation in practice. The results show that legal protection for honorary teachers is manifested through employment agreements as the basis of legal relations; however, its implementation is not yet optimal, as there are still teachers who do not have employment agreements and whose rights have not been fully fulfilled. The implications of this study emphasize the need to strengthen policies and coordination among stakeholders to ensure legal certainty and the welfare of honorary teachers.